Studi Pendekatan Dilemmas Stories pada Materi Hidrolisis Garam dengan Metode Thinking Aloud Pair Problem Solving (TAPPS) - Evi Elfrida; Tritiyatma Hadinugrahaningsih; Yuli Rahmawati (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This study aims to investigate the application and implication of Dilemmas Stories approach on the Salt Hydrolysis subject by using Thinking Aloud Pair Problem Solving (TAPPS) method toward students’ soft skills. The population of the study is 36 of public senior high school’s students at Jakarta. The study was conducted from February to April in 2015. The dilemmas stories which used in this study was the dilemmas of the use of fertilizer, Sodium Nitrite in processed meats, bleach apparel, and rice bleacher. This study was used a qualitative method by using multiple data collection techniques through the interview, reflective journal and classroom observation which is supported by CCVLES questionnaire with indicators, namely: feeling related to the story, story’s contents, teacher’s support, teamwork, empathetic communication, critical thinking, and contextual chemistry. The quality standards which used was credibility by using prolonged engagement, progressive subjectivity, and member checking. The results of the study have shown that the indicators in CCVLES were achieved. Moreover, it was also found other soft skills as the implication of learning which are motivation, the reflection of the values, curiosity, responsibility, and encourage to argue. The implication of the creativity was perceived by students both by poster and drama output. This study also discovered that there some preparation needed in applying Dilemmas Stories approach, including teacher’s practice, time efficiency, and appropriate materials selection. Thus, it can be concluded that Dilemmas Stories approach can be applicated in chemistry learning. Keywords: Dilemmas Stories, Salt Hydrolysis, Thinking Aloud Pair Problem Solving, CCVLES